An investigation of the effects of budgetary controls on firm performance: case study TSF - Chikuvadze, Wayne (Midlands State University, 2015)
The research was carried out with the aim of investigating the effects of budgetary controls on Tobacco Sales Floor’s performance during the period from 2011 to 2013. Although the TSF made profits during these years targeted performance were not met. TSF reports indicated that it is having difficulties in implementing its budgetary controls resulting in experiencing adverse variance in its expenditure for the past three to four years hence necessitated this research. Quantitative and qualitative data was collected. The sample size of 40 was used to carry out the study. The data presentation and analysis showed method of controlling cost, problems associated with budgetary controls and ways to improve TSF performance through the use of budgetary controls. Major findings were lack of staff training on budgetary controls, inflexibility of the budget structure and failing to constantly monitor feedback. The researcher suggested recommendations were that TSF staff should have a financial training on the budgetary controls has the organisation adopted and how they can be used to have a positive impact on the TSF’s performance. Furthermore in a world of continuous and uncertainties’ especially in agriculture where there many factors like climate, TSF should make use of the flexible budgetary controls. And finally TSF should have a continuous monitoring of results, which is weekly monitoring as it is associated with large volumes of data per day, any slack can be an opportunity for fraud.